Recipe optimization of vegetable pasta with iodine-containing raw material - Пересічний, Іванович Михайло; Паламарек, Каріна Вікторівна (Technology audit and production reserves, 2016)
The article discusses the relevance of developing technology for vegetable pastes with iodine-containing raw materials for the prevention of iodine deficiency disorders. Some the results of own research in this area are shown. The main purpose of the study is to optimize the recipe of vegetable pastes with iodine-containing raw materials to meet the food needs of indigenous people through mathematical processing of experimental data. Based on the author’s research and taking into account the data contained in this article, ingredient composition of vegetable paste with a high content of iodine and nutrients-synergists based on the use of protein and plant material were grounded and developed. Consistency of the developed vegetable pastes enables using them to prepare sandwiches, banquet decoration snacks, as mince and stuffing for cheese, potato rolls, pastry and so on. The research allowed to develop recipe and manufacturing process of obtaining rolls with vegetable pasta with iodine-containing raw material, which is enshrined in the approved technical specifications: TU U 10.8-05476322-002:2013 «Culinary products. Rolls with vegetable stuffing» and technological instructions for TU U 15.8-32214657-003:2010 «Culinary products. Rolls with vegetable stuffing». Thus, the broad interpretation of the problem of iodine deficiency and results of our study can be used not only specialists in nutrition and food, but endocrinologists and other doctors. This allows us to recommend developed culinary products to prevent iodine deficiency disorders.